'A Terrific Ogre': The Role of the Devil in Victorian Popular Belief. Issue 3 (3rd July 2017) - Bartels, Sarah
Abstract: The Devil played a vital role in Victorian popular belief. He was a multifaceted figure who could be humorous or terrifying, depending on the occasion. While he struggled for space with an array of supernatural figures, the Devil managed to maintain a presence in a wide variety of supernatural narratives and beliefs.